Technique and energy losses in front crawl swimming - Berger, M. A.; Hollander, A. P.; de Groot, G. (Medicine & Science in Sports & Exercise, 1997)
Although lift and drag forces occur during propulsion in swimming, the authors propose that lift is beneficial because of the relative small energy loss to the water. Consequent assumptions in this article contend that lift is the primary component of propulsive forces and decisions and the investigation design are based on that tenet.